Evidence-based weight-bearing protocols after meniscal repair: balancing functional recovery and healing safety across injury types - Maodong Wu; Qinglun Su; Qin Zhao; Shouguo Liu (Journal of Orthopaedic Surgery and Research)
Abstract Weight-bearing activity was the primary rehabilitation problem after knee meniscus repair, a scientific weight-bearing protocol was an important guarantee for injury healing and functional improvement. With the popularization of the concept of enhanced recovery after surgery, accelerated weight-bearing activities after knee meniscus repair surgery had gradually gained clinical promotion. However, the effectiveness and safety of accelerated weight-bearing activities were still controversial, and the appropriate weight-bearing protocol after knee meniscus repair with different injury types was still unclear. In this paper, we aimed to explore the decision-making elements of weight-bearing protocols after knee meniscus repair, and explore the effectiveness and safety of different weight-bearing protocols based on knee meniscus injury classification, providing evidences for clinical decision-making.